Approved Mental Health Professionals: Teamwork, 'Safety Nets' and 'Buckling Under'. - Hemmington, Jill (Journal of Social Work Practice, 2024)
In England and Wales, Approved Mental Health Professionals (AMHPs) have the ultimate responsibility, based on doctors' medical recommendations, for deciding to detain a person, without consent, under the Mental Health Act (1983). The work can be traumatic, yet its emotional impacts are often unacknowledged. Consistent themes include erratic levels of supervision and an overdependence on peer support, despite the longstanding recruitment and retention difficulties arising from high levels of stress and burnout. This article draws on findings from two research projects with AMHP services: one a national study using questionnaires and focus groups, and the other a doctoral research study using ethnography. Findings suggest that a lack of peer support, teamwork and debrief opportunities, exacerbated during the COVID-19 pandemic, intensified stress and burnout ('buckling under') as well as undermining socialising opportunities for trainees. AMHPs used metaphoric language to articulate their difficult experiences. Workplace environments including hot-desking and lone working may undermine casework discussions, social relations, informal peer support and supervision. Overall, AMHPs perceive their teammates as an essential source of support (a 'safety net') without which there are negative implications for practice. Ultimately, stress is exacerbated when there is no space to reflect and no team to do this with.